Rural migrants' participation in old-age insurance: a case study of the inter-provincial migrant workers from Sichuan, China. Issue 2 (3rd April 2017) - Chen, Yong; Tan, Yan; Zhang, Qin
ABSTRACT: Old-age pension, a fundamental part of the Chinese social security system, is perceived by the Chinese government as the last support for rural-to-urban migrant workers upon retreating from the labor market. Using survey data collected by the authors, this paper examines a host of factors which influence migrant workers' participation in the old-age scheme. The result shows that individual characteristics, employment status, attitudes toward old-age support and perception of the old-age pension system significantly differentiate two groups of migrant workers between those that have participated in and their counterparts who have not participated in the old-age pension schemes. Among a number of factors, age, educational attainment, holding labor contract, etc. are found to be significant factors influencing migrants' behavior participating (or not participating) the available age-pension schemes. Policy implications for how to improve the rate of participation in existing old-age pension schemes among migrant workers are drawn from the findings.